Caribbean drugs : from criminalization to harm reduction - Klein, Axel, 1961-; Day, Marcus; Harriot, Anthony (Zed Books in association with Drugscope ; Distributed exclusively in the U.S. by Palgrave ; Ian Randle, 2004)
In recent years Caribbean countries have responded to US pressure by adopting a coordinated policy of criminalizing ganja & crack cocaine usage. This volume assesses the impact of the policy on a population for whom drug usage has been socially acceptable & provides a warning for policy makers elsewhere.